Comparison of the effectiveness of individual emotion-focused therapy with emotion-focused therapy using art on rumination in people with love trauma syndrome - Aryannejad, Shirin; Salehi, Mahdieh; Taghiloo, Sadegh; Esteki, Mahnaz (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of the present study was to compare the effectiveness of individual emotion-focused therapy with emotion-focused therapy using art on rumination in people with love trauma syndrome. Methods: The method of this quasi-experimental study was a pretest-posttest design with a control and quarterly follow-up group. In order to select the participants of the study, 51 people with love trauma syndrome were selected by purposeful sampling method from among three psychological clinics in Tehran's second district according to inclusion and exclusion criteria and were randomly assigned to experimental and control groups (17 people in each group). The first experimental group received 12 sessions of individual emotion-focused therapy, the second experimental group received 12 sessions of emotion-focused using art, while the control group did not receive any intervention. In three stages of pre-test, post-test and follow-up of ruminant response scale Nolen-Hoxma and Moro (1991) were completed by participants to collect data. Data were analyzed using repeated measures analysis of variance. Results: The results showed that the effectiveness of emotion-focused therapy with the use of art and individual emotion-focused therapy on rumination in people with love trauma syndrome were significant in post-test scores and emotion-focused therapy with the use of art was more effective than individual emotion-focused therapy (F=13.17, p=0.001); Also, the changes resulting from emotion-focused therapy with the application of art and individual emotion-focused therapy remained on all three components three months after the end of the Paper treatment period. Conclusion: The results of the present study can be a basis for applying art in psychological therapies to make therapies more effective for applied psychologists.